TATA GUNA LAHAN DAN KEJADIAN BANJIR DI KAWASAN PERKOTAAN KABUPATEN TABALONG - Ria Tahfazona; Fadly H. Yusran; Syarifuddin Kadir; Akhmad Rizali Saidy (EnviroScienteae, 2022)
The Regional Spatial Plan (RTRW) is a direction in space utilization and control of space utilization, but the RTRW still uses a small scale of 1: 50,000, which means that information on topographical conditions is not described in detail, so the housing planning and licensing are not informed in detail as a result, low-lying areas Initially functioned as a temporary water reservoir turned into a residential area, it was unavoidable. The conventional drainage concept currently applied in Tanjung urban area is an effort to dispose of or drain excess water as soon as possible to the nearest river, namely the Mangkusip River. Along with the development which is not balanced with good drainage planning causes water to flow improperly, and high-intensity rainfall may occur flooding. The purpose of the research is to examine land use in urban areas with three-dimensional spatial data related to flood events, analyze flood events in urban areas, and determine locations as protected areas for water conservation. Three-dimensional spatial data using DEM from DEMNAS, the digital image in 2020. Determining protected location areas (jungle cities) using several parameters, where each parameter has its score value, both analyzes utilize GIS. Counting of a flood using Rational and Manning method. The results showed: 1) Topographic conditions and the slope of the research site, 2) Natural formation network of the Mangkusip river and tributary, 3) Length (L) Length of air traffic from the farthest point to the point at the review point, 4) The catchment area (A) from the modeling results, 5) The average slope of the water path from the farthest point to the observation point. 6) Land use (C), 7) The runoff flood discharge is greater than the flood discharge from the Mangkusip river reservoir, resulting in flooding, 8) From the results of the assessment with overlay scoring, the result is an area of 59,318 hectares for water conservation areas to prevent flooding.